Targeting SARM1 as a novel neuroprotective therapy in neurotropic viral infections - Sheng He; Yanyan Zhu; Xinyue Wang; Gaofeng Zhang; Kaijian Hou; Xianzhu Xia; Zhenyou Jiang; Xiaoqian Gong; Pingsen Zhao (Journal of Neuroinflammation)
Abstract Viral encephalitis, resulting from neurotropic viral infections, leads to severe neurological impairment, inflammation, and exhibits high mortality rates with poor prognosis. Currently, there is a lack of effective targeted treatments for this disease, which poses a significant public health concern. SARM1 has been identified as the pivotal mediator of axonal degeneration and inflammation across various neuropathies, activated by an elevation in the NMN/NAD+ ratio. However, comprehensive in vivo investigations into the role of SARM1-mediated pathogenesis in viral encephalitis are still lacking. In this study, we established mouse models of viral encephalitis using Japanese encephalitis virus (JEV), herpes simplex virus-1 (HSV-1), and rabies virus (RABV) as representative pathogens. Our findings demonstrate that neurotropic virus infections elicit robust axonal degeneration, mitochondrial dysfunction, and profound neuropathological damage in cortical neurons via the activation of SARM1. In mouse models of viral encephalitis, deletion or inhibition of SARM1 effectively preserved axonal morphology and maintained mitochondrial homeostasis, while also attenuating the infiltration of CD45+ leukocytes in the cortex. Consequently, these interventions ameliorated neuropathological damage and enhanced survival outcomes in mice. Our findings suggest that SARM1-mediated axonal degeneration and brain inflammation exacerbate the pathological progression of viral encephalitis. Therapies targeting SARM1 emerge as viable and promising strategies for protecting neuronal function in the context of neurotropic viral infections.